Low prevalence of ideal cardiovascular health in Peru. Issue 15 (11th January 2018) - Benziger, Catherine P; Zavala-Loayza, José Alfredo; Bernabe-Ortiz, Antonio; Gilman, Robert H; Checkley, William; Smeeth, Liam; Malaga, German; Miranda, Juan Jaime
Abstract : Background: The prevalence of and factors associated with ideal cardiovascular health (ICH) by sociodemographic characteristics in Peru is not well known. Methods: The American Heart Association's ICH score comprised 3 ideal health factors (blood pressure, untreated total cholesterol and glucose) and 4 ideal health behaviours (smoking, body mass index, high physical activity and fruit and vegetable consumption). ICH was having 5 to 7 of the ideal health metrics. Baseline data from the Center of Excellence in Chronic Diseases, a prospective cohort study in adults aged ≥35 years in 4 Peruvian settings, was used (n=3058). Results: No one met all 7 of ICH metrics while 322 (10.5%) had ≤1 metric. Fasting plasma glucose was the most prevalent health factor (72%). Overall, compared with ages 35–44 years, the 55–64 years age group was associated with a lower prevalence of ICH (prevalence ratio 0.54, 95% CI 0.40 to 0.74, P<0.001). Compared with those in the lowest tertile of socioeconomic status, those in the middle and highest tertiles were less likely to have ICH after adjusting for sex, age and education (P<0.001). Conclusion: There is a low prevalence of ICH. This is a benchmark for the prevalence of ICH factors and behaviours in a resource-poor setting.